Application of Principal Component Analysis on Factors Causing Inflation in West Kalimantan - Asri Rahmawati; Yuyun Eka Pratiwi; Onelia Rochmah (Komputasi: Jurnal Ilmiah Ilmu Komputer dan Matematika, 2025)
Inflation is an important indicator in assessing the economic stability of a region. Inflation fluctuations in West Kalimantan are influenced by various economic and structural factors. This study aims to identify the main factors causing inflation in West Kalimantan using Principal Component Analysis (PCA). Secondary data for the 2024 timeframe was obtained from West Kalimantan's Central Statistics Agency (BPS). Economic variables that are suspected of influencing inflation are analyzed using PCA to be reduced to new dominant factors. The main components obtained are then interpreted economically to understand the structure of the causes of inflation. The results of the analysis show that the cumulative proportion of the two components reaches 90%, so the two main components are sufficient to represent the main structure of the data. This means that most of the information from the original variables can be effectively reduced into two main components. Keywords: Inflation; PCA; reduction; economic factors.